Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/admt.202000780
|View full text |Cite
|
Sign up to set email alerts
|

Coco Stretch: Strain Sensors Based on Natural Coconut Oil and Carbon Black Filled Elastomers

Abstract: A biocompatible inexpensive strain sensor constituting of an elastomer filled with natural coconut oil (CNO) and carbon black (CB) is presented here. Strain sensors are widely utilized for applications in human activity recognition, health monitoring, and soft robotics. Given that these sensors are envisioned to be present in a plethora of fields, it is important that they are low cost, reliable, biocompatible, and eco‐friendly. This work demonstrates that CNO can be used to create conductive percolation netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…[ 43–45 ] Carbon black (Nouryon, Ketjenblack EC‐600JD), a type of conductive nanofiller, was infused with the thermoplastic polyurethane to improve the mechanical and electrical characteristics without losing biocompatibility, [ 53 ] although a detailed biocompatibility study was not performed. However, carbon black has already been used for biocompatible strain sensors and flexible bioelectrodes, [ 50,51 ] and the one used in this study showed high cell viability (100%) at a concentration of 32.5 µg mL −1 during an in vitro cytotoxicity study. [ 52 ] Additionally, as there is no evidence that the CSMP composite is nontoxic, an in vitro cytotoxicity test was performed (according to ISO 10993–5:2009 Biological Evaluation of Medical Devices – Part 5).…”
Section: Resultsmentioning
confidence: 99%
“…[ 43–45 ] Carbon black (Nouryon, Ketjenblack EC‐600JD), a type of conductive nanofiller, was infused with the thermoplastic polyurethane to improve the mechanical and electrical characteristics without losing biocompatibility, [ 53 ] although a detailed biocompatibility study was not performed. However, carbon black has already been used for biocompatible strain sensors and flexible bioelectrodes, [ 50,51 ] and the one used in this study showed high cell viability (100%) at a concentration of 32.5 µg mL −1 during an in vitro cytotoxicity study. [ 52 ] Additionally, as there is no evidence that the CSMP composite is nontoxic, an in vitro cytotoxicity test was performed (according to ISO 10993–5:2009 Biological Evaluation of Medical Devices – Part 5).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that carbon−based polymer sensors have received widespread attention, current research has focused mainly on the manufacture of the device and the sensing behavior [ 11 , 12 , 13 , 14 ] while research on its sensing mechanism is limited. In the initial research, an analogy method was proposed to quantitatively describe the electromechanical behavior of silicone rubber filled with CNPs, but the sensing mechanism was not involved [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[31] And sensors integrated temperature, humidity, pressure, stress responses and so on are obtained. [32][33][34][35][36][37] For instance, Crispin et al successfully developed a cellulose aerogels-based sensor enable pressure,…”
Section: Introductionmentioning
confidence: 99%